Lexicography in Australia - Delbridge, A. (Lexikos, 1992)
This paper describes the current setting for lexicography in Australia by reviewing the place of English since the first British settlement began, in 1788. The emergence of Australian English as the national language is traced, and its relations with the Australian Aboriginal languages touched on. The greatest change in the language setting came with Australia's immigration policy in its post-World War II form. This resulted in the government's eventual recognition of Australia as multilingual and multicultural, and urgently in need of a formal policy on languages, one which treated the many community languages of Australia as an economic, social, educational asset. The paper then summarises the past and present record of lexicography, in Australian English, in Aboriginal and community languages, and in languages of its neighbours in the Pacific area. Titles of some of the most important dictionaries are listed in the bibliography. It ends by describing the outlook of the newly formed Australasian Association for Lexicography.